The first cat in space and the wrath of the paperclip - Barnett, Mac (Barnett, Mac. First cat in space, 2024)
CheckMate, an AI paperclip designed to fix grammatical errors, wants to turn carbon-based lifeforms into paperclips, so when he invades every computer, the First Cat in Space, the Moon Queen, and LOZ 4000 come to help.